Criminologists on The Causal Factors of Unreported Narcotics Crimes - Muhammad Merpi Agung Perkasa (Ius Poenale, 2023)
Efforts to overcome and eradicate narcotics crimes require community participation, especially in reporting narcotics crimes. Some people don't want to report knowing that there is a narcotic crime. The problem of this research is whether the factors that cause crime do not report the existence of narcotic crime and how our efforts to deal with crime against crime not reporting narcotic crime. This research uses normative juridical and empirical juridical approaches. Data collection procedures were carried out using literature and field studies; the data were analyzed qualitatively to obtain conclusions and suggestions. An example of a crime not reporting the existence of a narcotics crime with permanent legal force is in Decision Number: 522/Pid.Sus/2022/PN Tjk with the defendant Ali Amarsyah Bin Misran being imprisoned for 8 (eight) months because it was proven legally and convincingly committing the crime of Article 114 of the Narcotics Law. The results of the research and discussion show that: Factors that lead to crimes not reporting narcotics crimes consist of the community does not want to deal with legal issues because they are considered to be a hassle for themselves, the community being afraid of the perpetrators of criminal acts and their syndicates which have the potential to threaten the safety of their lives if known reporting narcotics crimes and the lack of public understanding of the legal protection they will get if they report narcotics crimes to law enforcement. Efforts to overcome crime by not reporting the existence of narcotics crimes non-prenatally are by conducting counseling on legal awareness to the public so that people are willing to become reporters of narcotics crimes and provide security and safety guarantees for reporters. Penal efforts are carried out by a process of inquiry and investigation. Investigators take action in matters and according to the manner regulated in this law to seek and collect evidence with that evidence to shed light on the crime that occurred and to find suspects who have not reported a narcotics crime.